Three decades of change: exploring colonial legacies and shifts within processes of admission at South African Universities of Technology - Kemm-Stols, Lyndall Elizabeth (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning)
Given South Africa's complex legacy of inequality, access to higher education remains a priority for the government, higher education institutions and the public. And while significant progress has been made in terms of increased participation and expanded opportunities, particularly at Universities of Technology (UoTs), disparities remain. This particular type of institution has played a key role in contributing to the redress agenda through their less stringent admission requirements, but they remain underexamined in broader higher education literature. Despite these contributions, marginalised or working-class communities in rural and impoverished areas continue to face significant challenges in accessing higher education. Set against a global backdrop where similar patterns of admission have emerged, it becomes important to understand how and why the processes of admission in UoTs have emerged through the last three decades. In so doing, this study seeks to contribute to the conversation around social justice in higher education, offering insights that could reshape the understanding of why things are the way they are. This study draws on Critical Realism more broadly and the tools of Social Realism specifically to explore how South Africa's particular colonial legacy remains one of many hidden mechanisms on which we build our reality. Using various documentation and qualitative data generated through interviews, which was analysed using Social Realism's morphogenetic framework, I have endeavoured to tell the story of how, Universities of Technologies and their processes of admission have changed over the last three decades. In so doing I have shown, through using a metaphor of 'The House Modernity Built' how although much change has happened, hidden structures and cultures have worked to maintain a certain status quo, thereby constraining redress. This study has outlined the emergence of UoTs and their processes of admission as we understand them today. Through this I have presented an argument which suggests that the higher education sector continues to be structured in a hierarchical manner with UoTs located at the bottom. Mechanisms manifesting from a broader neoliberal environment, such as the higher education funding formula and global university ranking systems have placed UoTs in a position where they need to 'catch up', having consequences on the way in which processes of admission have been conceptualised. This has seen English becoming a marker of quality, and diploma offerings being replaced with degree equivalents carrying higher admission criteria, all of which work to compromise the redress needed in South African higher education.
Keywords: Education, Higher -- South Africa; Technical education -- South Africa; Universities and colleges Admission; Decolonization; Social realism; Educational equalization -- South Africa